2019
DOI: 10.1111/apa.15093
|View full text |Cite
|
Sign up to set email alerts
|

Self‐reported mental health and cortisol activity at 27‐28 years of age in individuals born with very low birthweight

Abstract: Acta Paediatrica. 2020;109:948-958. wileyonlinelibrary.com/journal/apa

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Interestingly, former very preterm/very low birthweight (VP/VLBW) adults perceived their relations with partners and family and their experience of work and education as similar to those in the former term control group, while they had lower ratings in their relationships with friends [42]. The self-reported mental health was comparable between former preterm and term infants [43]. A study from Switzerland showed no difference in the health related quality of life (HRQoL) of former preterm infants compared to term counterparts, even though they did tend to have more chronic diseases [44].…”
Section: Outcome Measuresmentioning
confidence: 99%
“…Interestingly, former very preterm/very low birthweight (VP/VLBW) adults perceived their relations with partners and family and their experience of work and education as similar to those in the former term control group, while they had lower ratings in their relationships with friends [42]. The self-reported mental health was comparable between former preterm and term infants [43]. A study from Switzerland showed no difference in the health related quality of life (HRQoL) of former preterm infants compared to term counterparts, even though they did tend to have more chronic diseases [44].…”
Section: Outcome Measuresmentioning
confidence: 99%
“…A regional Swedish cohort of 56 adults born with very low birthweight (VLBW) reported their self‐rated mental health at 27‐28 years of age. This showed that it was comparable with 55 controls with a normal birthweight 2 . The study by Leijon et al found that VLBW females had higher morning salivary cortisol concentrations than the controls, but no significant associations were found between those concentrations and the adult self‐reported scales.…”
Section: Mental Health and Cortisol Activity In Adults Born With A Vementioning
confidence: 78%